Application of Operations Research in Health System of Iran - Kourosh Eshghi; Maryam Rastegar (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2005)
In this paper first a brief literature survey on applications of operations research in health care systems is presented. Then two problems the optimal allocation of ambulances and the scheduling of nursing personnel are discussed in details. Finally these two models will be applied on two real cases in iranian health care system.